PREVALENCE OF ANTIBODIES TO HEPATITIS C VIRUS IN HEMODIALYSIS PATIENTS - Turgay ARINSOY; Halis ŞİMŞEK and Nurol ARIK and Ünal YASAVUL and Çetin TURGAN and Şali ÇAĞLAR and Hasan TELATAR (Turkish Journal of Gastroenterology, 2020)
-